2015
DOI: 10.1073/pnas.1418216112
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of the androgen receptor in polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is one of the most common female endocrine disorders and a leading cause of female subfertility. The mechanism underlying the pathophysiology of PCOS remains to be illustrated. Here, we identify two alternative splice variants (ASVs) of the androgen receptor (AR), insertion and deletion isoforms, in granulosa cells (GCs) in ∼62% of patients with PCOS. AR ASVs are strongly associated with remarkable hyperandrogenism and abnormalities in folliculogenesis, and are absent from all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 43 publications
4
66
1
3
Order By: Relevance
“…More recently, genomic information was reported from women with PCOS by GWAS studies (48, 49). While we did observe changes in AR expression, which displays altered expression in a cohort of women with PCOS (50), there were no changes in mRNA levels of the recently identified PCOS-associated mRNA DENND1A (48). The function of DENND1A is in membrane associated endocytosis and receptor trafficking; there is some evidence that expression of a DENND1A variant increases androgen production in a human theca cell model (51).…”
Section: Discussioncontrasting
confidence: 86%
“…More recently, genomic information was reported from women with PCOS by GWAS studies (48, 49). While we did observe changes in AR expression, which displays altered expression in a cohort of women with PCOS (50), there were no changes in mRNA levels of the recently identified PCOS-associated mRNA DENND1A (48). The function of DENND1A is in membrane associated endocytosis and receptor trafficking; there is some evidence that expression of a DENND1A variant increases androgen production in a human theca cell model (51).…”
Section: Discussioncontrasting
confidence: 86%
“…Multiple regulatory elements have been observed in Cyp19a promoter in zebrafish (Zhao et al, 2017). Wang et al (2015c) demonstrated that diminished binding of the androgen-androgen receptor complex to the androgen responsive element in Cyp19a1 promoter resulted in suppression of aromatase expression. Similarly, down-regulated estrogen would be expected to decrease the binding to the estrogen responsive elements in Cyp19a promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, AR had been suggested to regulate signaling pathways occurring in granulosa cells, and granulosa cells-specific AR appeared to promote preantral follicle growth and prevent follicular atresia, it was essential for normal follicular development and fertility (Sen and Hammes, 2010;Duggavathi and Murphy, 2009). Recent reports have documented that AR was widely believed to be an important regulator of granulosa cells biology, high expression of AR in granulosa cells was primarily considered to associate with PCOS (Yang et al, 2014;Wang et al, 2015). While androgen excess enhanced follicular development and dysfunction formation of antral follicles leading to PCOS, low androgen levels may be associated with abnormalities of follicular growth (Prizant et al, 2014).…”
Section: Introductionmentioning
confidence: 99%